Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.26773/mjssm.220306
|View full text |Cite
|
Sign up to set email alerts
|

Match Running Performance of Brazilian Professional Soccer Players according to Tournament Types

Abstract: The present study aimed to report different level games in terms of their external game loads, using data collected from GPS performance indicators in Brazilian soccer teams. We used measures of 464 performances of professional soccer athletes during the National Tournament (NT=265), State Tournament (ST=89), National Cup (NC=44), and the International Tournament (IT=66). The performance analysis included the assessment of Total (meters) and Relative (meters/minutes) distances; running (>14km/h), and sprint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Mixed Martial Arts (MMA) is a comprehensive combat sport that combines techniques from various martial arts disciplines, encompassing striking (e.g., boxing and kickboxing) (Miarka et al, 2020) and grappling (e.g., Brazilian Jiu-Jitsu and wrestling) (Bello et al, 2019). MMA competitors employ striking and grappling techniques while standing and on the ground (Fernandes et al, 2022). MMA fights are structured into rounds, each lasting several minutes, significantly demanding the athletes' cardiovascular endurance (Spanias et al, 2019;Gottschall and Hastings, 2023).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mixed Martial Arts (MMA) is a comprehensive combat sport that combines techniques from various martial arts disciplines, encompassing striking (e.g., boxing and kickboxing) (Miarka et al, 2020) and grappling (e.g., Brazilian Jiu-Jitsu and wrestling) (Bello et al, 2019). MMA competitors employ striking and grappling techniques while standing and on the ground (Fernandes et al, 2022). MMA fights are structured into rounds, each lasting several minutes, significantly demanding the athletes' cardiovascular endurance (Spanias et al, 2019;Gottschall and Hastings, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Weight divisions are classified as flyweight (−57 kg), bantamweight (−61 kg), featherweight (−66 kg), lightweight (−70 kg), welterweight (−77 kg), middleweight (−84 kg), light heavyweight (−93 kg), and heavyweight (−120 kg) (UFC, 2023b;UFC, 2023a). The main differences between weight categories typically include the fighters' size, strength, and fighting style (Fernandes et al, 2022;Folhes et al, 2023). Time-motion analysis can vary significantly between divisions as well (Miarka et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, Henríquez et al [ 11 ], explored the difference in the physical response of international footballers with CP, suggesting that players from top-ranked teams playing against teams of similar level reported higher physical demands, as did bottom-ranked teams playing against teams of equivalent rank. In much that same way, the physical responses of the referees who officiated World Cup matches have been higher than the physical responses registered by the referees of the World Championships, given that in conventional football, it has also been observed that the players of higher competitive level register higher physical responses [ 36 , 37 ]. The fact that players belong to a higher competitive level implies that they are exposed to greater physical responses [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…In much that same way, the physical responses of the referees who officiated World Cup matches have been higher than the physical responses registered by the referees of the World Championships, given that in conventional football, it has also been observed that the players of higher competitive level register higher physical responses [ 36 , 37 ]. The fact that players belong to a higher competitive level implies that they are exposed to greater physical responses [ 36 , 37 ]. The present results suggest that referees must, at minimum, be prepared for the base level requirements demanded by the type of competition but ultimately should be prepared for the highest levels of demands that the competition can provide in order to meet the demand of the players they are officiating.…”
Section: Discussionmentioning
confidence: 99%
“…The rst study showed that lower divisions (i.e., 3rd and 4th National League) presented higher physical demands than upper state standards (1st São Paulo division) . The second study revelated that International (Libertadores Cup) and National (1st National League) Tournaments exposed higher external load than state-level (1st Rio de Janeiro division) (Freire et al, 2022). Therefore, more studies are needed to inform internal and external load during elite Brazilian national leagues (e.g., 1st and 2nd National League), including other contextual factors.…”
Section: Introductionmentioning
confidence: 99%